Situation Report: Poland, 17 March 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Authorities Begin a Limited Appraisal of the Events of 1968 Official Trade Unions Criticize Industrial Work and Health Conditions Health-Care Workers Petition for Higher Wages Unabated Emigration of the Young Worries the Government and the Church Poland Courts Its Émigré Writers Deputy Raises the Issue of Katyn in the Sejm Miscellaneous Items